Insights into past land-use and vegetation change in the Llanos de Moxos (Bolivia) using fungal non-pollen palynomorphs. (June 2021) - Loughlin, Nicholas J.D.; Mayle, Francis E.; Nuñez Otaño, Noelia B.; O'Keefe, Jennifer M.K.; Duncan, Neil A.; Walker, John H.; Whitney, Bronwen S.
Abstract: Here we document a 1000-year fungal record from the raised-field region of the Llanos de Moxos, a seasonally inundated forest-savanna mosaic in the Bolivian Amazon. Fungi are extremely sensitive to changes in vegetation due to their close relationship with the local environment, providing a useful proxy for past local vegetation and land-use change. Here the remains of fungal non-pollen palynomorphs (NPPs) are identified from a sediment core taken from Laguna El Cerrito. A multivariate constrained ordination is used to extract relationships between the fungal NPP types and environmental gradients, specifically, tree cover, near-shore vegetation, crop cultivation, burning and local sediment input. NPP types such as Neurospora cf. cerealis are identified as indicative of pre-European agriculture and offer the ability to expand on the temporal range of cultivation in the raised-field region. Constrained cluster analysis indicates that the most significant changes in the NPP assemblage occurs c. 1500 and c. 1700 CE, corresponding to the arrival of Europeans to the Americas and Jesuit missionaries to the Llanos de Moxos respectively. The modern savanna landscape is one shaped by changes in land-use and the introduction of cattle following the European Encounter. Highlights: Significant change in past vegetation and land-use in the Llanos de Moxos occurred c. 1500 CE, following European arrival. The crop fungal spore Neurospora cf. cerealis can be used as supporting evidence of local pre-Columbian maize agriculture. The modern savanna was shaped following the arrival of Jesuit missionaries to the Llanos de Moxos c. 1700 CE.